Basic Skill Levels In Playing Futsal Among Extracurricular Participants at SD Negeri Karangtalun 05 - Akbar R.H, Muhammad Rizky; Saefulah, Dian Imam; Kusmiyati, Kusmiyati; Yulianto, Ari Gana; Haris, Iyan Nurdiyan (Indonesian Journal of Physical Activity, 2024)
This study aims to evaluate the basic futsal skills of the extracurricular participants at the school. This research is a descriptive quantitative study that employs a survey method and data collection techniques through testing. The subjects of the study consist of futsal extracurricular students aged 10-12 years at SD N Karangtalun 05, totaling 20 participants. The instrument used is a basic futsal skills test model for the 10-12 age group developed by (Wijayanti & Kushartanti, 2014). To assess the basic ability to play futsal, four test items are combined into one test series: dribbling, passing, controlling, and shooting. The data analysis technique applied in this study is descriptive quantitative, presented in the form of t-scores adjusted to the applicable norms. The results indicate that the level of basic futsal skills among participants in the extracurricular program at SD N Karangtalun 05 includes 5 students in the very good category, 11 students in the good category, 3 students in the moderate category, 1 student in the poor category, and no students in the very poor category.